Is Quail Hunting Self-Regulatory? Northern Bobwhite and Scaled Quail Abundance and Quail Hunting in Texas - Markus J. Peterson; Robert M. Perez (National Quail Symposium Proceedings, 2017)
Wildlife managers often maintain that quail hunting is self-regulatory because they assume hunters spend fewer days hunting, and bag fewer quail per day, when hunting is "poor," while hunting more frequently, and bagging more quail per day, when hunting is "good." For this reason, managers conclude that minor changes in hunting season length and bag limit are inconsequential. We used August quail abundance (1978-1996) and harvest (1981-1983, 1986—1996) data collected by Texas Parks and Wildlife Department biologists to test the "self-regulatory" hypothesis for both northern bobwhites (Colinus virginianus) and scaled quail (Callipepla squamata). First, we tested the hypothesis that quail abundance in August was sufficient to account for the total number of quail bagged by hunters during the subsequent hunting season. We then tested the hypotheses that quail abundance could predict: (1) the number of days people hunted quail; (2) the number of quail bagged per hunter per day; and (3) the number of quail hunters during the subsequent hunting season. Quail abundance in August was correlated with the number of northern bobwhite and scaled quail bagged during the following hunting season (r2 = 0.769 and 0.874, P <0.0005, respectively). Texas hunters typically hunted quail about 2.5 to 3 days annually regardless of quail abundance. Quail abundance in August, however, was correlated with the number of quail bagged per hunter per day and the number of quail hunters during the subsequent hunting season (northern bobwhite: r2 = 0.895 and 0.868, P <0.0005, respectively; scaled quail: r2 = 0.833 and 0.740, P < 0.0005, respectively). These results are consistent with the hypothesis that both northern bobwhite and scaled quail abundance can regulate quail hunting effort and success within the framework of the hunting regulations that have been in effect in Texas since the early l 980's.